Students Response to the Literacy Educational Game Application at SMPN 2 Kwanyar - Rohmah Naelur; Dwi Saputro Sigit; Azkal Uyun Nadia (SHS Web of Conferences)
The reading literacy scores of Indonesian students according to PISA are far below the global average. Efforts to improve literacy can be developed through learning media. One of the learning media that students like is educational games. The purpose of this research is to determine students' responses to the Literacy Educational Game (LEG) as a learning medium to foster literacy skills. The research method is quantitative descriptive. The subject of this research is the students of SMPN 2 Kwanyar, totaling 26 students. This research instrument includes a media validation sheet and a student response questionnaire. The results of the media expert validity showed a percentage of 87%, which falls into the very good category. Meanwhile, the results of the student response questionnaire showed a percentage of 90%, also falling into the very good category.